Peran Teknologi Informasi dalam Mendukung Ketahanan Ekonomi Daerah Rawan Bencana: Studi Literatur Berbasis Sustainable Development Goals (SDGs) - Hayatul Khairul Rahmat; Nurkholis Nurkholis; Muhammad Firjatullah Nur Akbar (PT Hakhara Akademia Indonesia, 2025)
Disaster-prone regions face serious challenges in maintaining economic sustainability and stability due to repeated disruptions to production systems, distribution networks, and community livelihoods. Economic resilience is a key element of sustainable development, particularly in the context of achieving the Sustainable Development Goals (SDGs). Along with the rapid development of Information Technology (IT), strategic opportunities have emerged to strengthen the capacity of disaster-prone areas to anticipate, respond to, and recover economic activities. This article aims to systematically examine the role of Information Technology in supporting the economic resilience of disaster-prone regions through an SDGs-based literature review approach. The method employed is a systematic literature review of reputable national and international journals published between 2015 and 2025. The findings indicate that IT plays a significant role in three main phases of disaster management: economic risk mitigation through information systems and early warning systems; strengthening economic response during disasters through communication technologies and digital platforms; and accelerating post-disaster economic recovery through MSME digitalization, fintech, and data-driven economic approaches. Nevertheless, the digital divide, limited infrastructure, low levels of technological literacy, and data security issues remain major challenges in implementing IT in disaster-prone areas. This article recommends the integration of digital transformation policies with disaster risk reduction strategies and sustainable economic development to strengthen SDGs-based economic resilience.